2017
DOI: 10.1364/oe.25.005797
|View full text |Cite
|
Sign up to set email alerts
|

53 W average power CEP-stabilized OPCPA system delivering 55 TW few cycle pulses at 1 kHz repetition rate

Abstract: We present a high peak and average power optical parametric chirped pulse amplification system driven by diode-pumped Yb:KGW and Nd:YAG lasers running at 1 kHz repetition rate. The advanced architecture of the system allows us to achieve >53 W average power combined with 5.5 TW peak power, along with sub-220 mrad CEP stability and sub-9 fs pulse duration at a center wavelength around 880 nm. Broadband, background-free, passively CEP stabilized seed pulses are produced in a series of cascaded optical parametric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(102 citation statements)
references
References 30 publications
2
94
0
6
Order By: Relevance
“…A broader, spectrally flat SC was produced using pump wavelengths around the zero GVD point of sapphire (1.31 μm) [206]. Such SC was used to seed the OPCPA system driven by diode-pumped Yb:KGW and Nd:YAG lasers, finally producing carrier envelope phasestable sub-9 fs pulses with 5.5 TW peak power at 1 kHz repetition rate [52]. In the range of anomalous GVD of sapphire, the SC spectrum spanning wavelengths from 470 nm to more than 2.5 μm were reported with 15 fs pulses at 2 μm, however, showing a noticeable drop of the spectral intensity around 1 μm [161].…”
Section: Laser Hostsmentioning
confidence: 99%
See 1 more Smart Citation
“…A broader, spectrally flat SC was produced using pump wavelengths around the zero GVD point of sapphire (1.31 μm) [206]. Such SC was used to seed the OPCPA system driven by diode-pumped Yb:KGW and Nd:YAG lasers, finally producing carrier envelope phasestable sub-9 fs pulses with 5.5 TW peak power at 1 kHz repetition rate [52]. In the range of anomalous GVD of sapphire, the SC spectrum spanning wavelengths from 470 nm to more than 2.5 μm were reported with 15 fs pulses at 2 μm, however, showing a noticeable drop of the spectral intensity around 1 μm [161].…”
Section: Laser Hostsmentioning
confidence: 99%
“…SC generation in laser host crystals with sub-picosecond and picosecond laser pulses paved a new avenue in the development of compact OPCPA systems, which are built around sole picosecond oscillator/amplifier systems [51]. Finally, the SC-seeded OPCPA system delivering carrier-envelope phase-stable few-optical-cycle pulses with high average and ultrahigh peak power has been recently demonstrated [52].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it could 120 7 Summary and outlook be shown that owing to the sub-picosecond pump pulse duration, there is no pedestal around the main peak (at least not longer than ∼1 ps), a crucial advantage of the PFS over OPCPA systems with longer pump pulse durations (e.g. [164,165]) especially for the key application of surface high-harmonic generation.…”
Section: Discussionmentioning
confidence: 99%
“…This applies also for the ambitious OPAL and XCEL projects that seek to bring OPCPA at moderate bandwidth to the kilojoule-level. , LWS-pro [107], Ecole Polytechnique [126], LWS20 [44], ELI-ALPS Sylos [165], CELIA [34], ELI-ALPS HF [167], Apollon 10 PW [40], OPAL [168], ATLAS [169], ELI-NP HPLS [39], SIOM-SULF [12,38], XCEL [170], Astra-Gemeni [171], BELLA [32], Vulcan [43,172], POLARIS [173], PENELOPE [174], Texas PW [31]. It should be noted that the plot does not provide any information about the repetition rate.…”
Section: High Peak-power Systems Worldwidementioning
confidence: 99%
See 1 more Smart Citation